2017
DOI: 10.1177/0022002717701181
|View full text |Cite
|
Sign up to set email alerts
|

Even Constrained Governments Take

Abstract: This article analyzes an understudied and contested form of government taking, transfer restriction, which has supplanted expropriation as the most ubiquitous and costly type of international property rights violation. Veto-player-type constraints curtail governments’ ability to engage in outright and (nontransfer related) creeping expropriation but have little impact on their ability to generate wealth via transfer restrictions. We use a formal model to derive testable implications regarding the effect of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Democracy's null results are consistent with other research showing that political factors are not useful in predicting credit crisis onset (Biglaiser, DeRouen Jr., and Archer 2011). In addition, our results contribute to a literature that demonstrates that domestic institutional constraints have a heterogeneous effect on political risk in the global economy (Graham, Johnston, and Kingsley 2018). Overall, the results in the first tier suggest that economic factors largely influence a state's decision to seek renegotiation with creditors.…”
Section: Resultssupporting
confidence: 87%
“…Democracy's null results are consistent with other research showing that political factors are not useful in predicting credit crisis onset (Biglaiser, DeRouen Jr., and Archer 2011). In addition, our results contribute to a literature that demonstrates that domestic institutional constraints have a heterogeneous effect on political risk in the global economy (Graham, Johnston, and Kingsley 2018). Overall, the results in the first tier suggest that economic factors largely influence a state's decision to seek renegotiation with creditors.…”
Section: Resultssupporting
confidence: 87%
“…Recently, scholars have concluded that this advantage likely stems from strong legal institutions (Biglaiser and Staats 2012;Biglaiser, Lee, and Staats 2017) and constraints on executive power in democracies, which enable policy makers to make credible commitments to investors (Jensen 2008;Li 2009). Credible commitments reduce the likelihood that a government will expropriate assets or impose limits on currency convertibility, which can be a form of "creeping expropriation" (Graham, Johnston, and Kingsley 2018). Political constraints also prevent power grabs and provide clear expectations for succession (Olson 1993), making armed political conflict less likely.…”
Section: Theoretical Expectationsmentioning
confidence: 99%
“…This issue is increasingly serious and affects how firms do business in emerging markets (e.g., Feinberg and Gupta, ; Garcia‐Canal and Guillen, ; Li and Zhang, ; Uhlenbruck et al , ) . State expropriation takes various forms, and can include any or all of the following: massive, country‐wide expropriation resulting from dramatic events such as war, violence, and political regime shifts; direct expropriation of private assets, typically without legal basis; and indirect or creeping expropriation that adversely affects a firm's revenue streams but may have legal bases, such as transfer risks, tax risks, and regulatory risks (Graham, Johnston, and Kingsley, ; Jensen, ; Jensen et al , ). While the latter two types of state expropriation are more prevalent in the modern era, the mechanisms at work are quite distinct and have thus yielded divergent predictions (e.g., Graham et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…State expropriation takes various forms, and can include any or all of the following: massive, country‐wide expropriation resulting from dramatic events such as war, violence, and political regime shifts; direct expropriation of private assets, typically without legal basis; and indirect or creeping expropriation that adversely affects a firm's revenue streams but may have legal bases, such as transfer risks, tax risks, and regulatory risks (Graham, Johnston, and Kingsley, ; Jensen, ; Jensen et al , ). While the latter two types of state expropriation are more prevalent in the modern era, the mechanisms at work are quite distinct and have thus yielded divergent predictions (e.g., Graham et al , ). To isolate the applicable mechanisms and the responses to these mechanisms, we focus in this article on direct expropriation by the state without legal basis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation